A produção do cuidado em saúde mental nos Centros de Atenção Psicossocial - CAPS: um olhar sobre os sistemas de informação, suas potências e seus limites - Muriano, Manuela Lazarini (2024)
In order to strengthen management and professional practice for monitoring within the Brazilian Unified Health System (SUS), particularly within the Psychosocial Care Network (RAPS), the Psychosocial Care Centers (CAPS) become the focus of this study, recognizing their strategic role in care provision and organization. Objectives: To broaden and enhance the discussion among workers from the 25 CAPS accredited by December 2021 in the DRS XVII - Taubaté region, regarding the production registration in DATASUS official information systems: BPA-I, RAAS, and BPA-C. Method: This is a participatory action research, exploratory in nature with a mixed-method approach, conducted in three stages: 1. identification of accredited CAPS in the delimited region, via CNES; 2. Elaboration of individualized reports by CAPS, with information on monthly production from 2018 to 2021, according to DATASUS records, accompanied by an invitation letter for the indication of CAPS professionals to participate in a focus group; 3. Conducting 2 Focus Groups, using an informative activity and a problem situation as triggering strategies. Results: Quantitative data were presented as a regional snapshot, grouped by CAPS modality and by DATASUS Data Capture System, without the intention of producing comparative analyses between services. These results revealed situations of absence of records and, particularly, the lack of linearity of records for CAPS of the same modality. In the analysis by Data Capture System, the low quantity of records in BPA-I, which represents the patient's first contact with the unit, is noteworthy; the significant number of records of individually focused actions through RAAS; and the lack of regularity in the records of procedures that identify the user's pathway and articulation with the Network, through BPA-C. The content of the focus groups with CAPS workers provided elements for the qualitative analysis organized into two thematic categories: Challenges for the production and systematization of information and Reflections on the particularities/specificities of work in CAPS. In the first category, it was observed that territorial singularities interfere with the systematic way in which records are made and the challenges of workers to register and handle various data capture systems with fragile interoperability among them. In the second category, the discussion about the registration of production information and the reliability of data raises issues such as the bureaucratization of the work process and the relevance of maintaining permanent multidisciplinary spaces for case discussion, as well as prioritizing frequent educational actions related to production registration in information systems. Conclusions: It is hoped that this study will encourage RAPS managers and workers to use data available in DATASUS official information systems for CAPS monitoring, critical analysis of RAPS, and collaborative construction of actions focused on community-based and individual-centered needs. As a proactive strategy for managers, recommendations were presented in the fields of work management, information management, and clinical management.